2013
DOI: 10.7243/2052-5966-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Program compliance, weight loss and health profile changes in WHO obesity classes after very low energy dietary intervention

Abstract: Background: To assess program compliance, weight loss and health benefits in different WHO obesity classes (Class I: BMI 30-34.9; Class II: BMI 35.0-39.9; Class III: BMI 40+) after a very low energy diet intervention. Methods: Obese participants (n=1012) attending a private weight control clinic enrolled in a 26 week program. The first 12 weeks involved restricted energy intake (800 kcal/day), then gradual reintroduction of normal food (1200-1300 kcal/day), in conjunction with behaviour management. Body mass i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…2,3 However, there is marked inter-individual variability in the success of this approach that has often been attributed to patient compliance. 4…”
mentioning
confidence: 99%
“…2,3 However, there is marked inter-individual variability in the success of this approach that has often been attributed to patient compliance. 4…”
mentioning
confidence: 99%
“…In most studies, compliance was measured using frequency of participation, and it was reported that the higher was the attendance rate, the greater were the effects of education and weight reduction. 17 In this study, we investigated the effects of a 12-week customized lifestyle-modification program known as "Change 10 Habits" on body fat composition and the impact of lifestyle habit changes on obesity management among South Korean adults with obesity.…”
Section: Introductionmentioning
confidence: 99%